Türkiye Doğal Bitki Örtüsünde Relik Bir Tür: Diospyros Lotus L. (Küçük Meyveli Trabzon Hurması) - (:unkn) unknown (My University, 2002)
0

Today, Diospyros lotus is one of the speciesof the Diospyros L. taxon which has a wide dispersal area in tropical and subtropical regions of the world and is sole naturally growing species in Turkey. Diospyros lotus, remmant of mild and humid climate of Tertiary, has a limited dispersal area at middleand eastern parts of Blacksea region. Here it is found mixed with Euxine and Mediterrannean types of elements on slopes facing Blacksea and in some valleys. Probably, the dispersal area of Diospyros lotus which was wider in Tertiary later diminished in Pleistocence due to climatic changes, Thus, Diospyros lotus gradually retreated to the present day parts where ecological conditions as a result of orography were established.